Marcas News Europe N° 4 : memórias intimas marcas project for MUHKA Antwerpen. - Boshoff, Willem; Bouschet, Gast; Carlos, Isabel; Fourie, Abrie; Geers, Kendell; Hernandez, Orlando; Kellner, Clive; Muteba Luntumbue, Toma; Richards, Colin; Vari, Minnette; van der Merwe, Jan (Antwerpen : M HKA (Museum van Hedendaagse Kunst Antwerpen), 2000)
Garaicoa, Carlos ; Mutima, N'dilo ; Bidjocka, Bill ; van der Merwe, Jan ; Richards, Colin ; Geers, Kendell ; Hassan, Kay ; Bouschet, Gast ; Muteba Luntumbue, Toma ; Fourie, Abrie ; Vari, Minnette ; Ntakiyica, Aimé ; Boshoff, Willem ; Alvim, Fernando
Marcas News Europe N° 4 : memórias intimas marcas project for MUHKA Antwerpen, M HKA (Museum van Hedendaagse Kunst Antwerpen) Antwerpen, 05.02 - 07.05.2000
Nederlands & Engels
kunstcatalogus